Barn som relasjonspartnere: Diskurser om det kulturelt adekvate barnet - Ulvik, Oddbjørg Skjær (Kvinder, Køn & Forskning, 2005)
Parental relationships are to a great extent theoretically naturalised, in psychology as well as in other social sciences. This article aims to analyse parental relationships as culturally and historically situated. The meaning of being a child and a responsible caregiver related to one another are negotiated in everyday life practices in continual care relationships between children and adults. Discourses of children and relationships are cultural tools for the participants of those practices. This paper will focus on adult expectations to children. The analysis is based on an interview study with adults and children living in foster families. In foster families, what is taken for granted in other families, will be more explicit. Thus, it is a strategic area to explore cultural meaning of adultchild relationships. The article elaborate “the discourse of the child with limited responsibility”, “the discourse of the child competent of reciprocity”, and “the discourse of the self constructing child”, discourses that are dynamically related.